A facile palladium-catalyzed route to 2, 5, 7-trisubstituted indoles. Issue 49 (9th December 2015) - Cacchi, Sandro; Fabrizi, Giancarlo; Goggiamani, Antonella; Iazzetti, Antonia; Verdiglione, Rosanna
Abstract: A facile and general approach to the synthesis of 2, 5, 7-trisubstituted indoles from readily available 2-bromo-6-iodo-4-substituted and 2-bromo-4-chloro-6-iodoanilines is reported. The assembly of the indole rings is accomplished via a one-pot Sonogashira cross-coupling with terminal alkynes followed by a palladium-catalyzed cyclization step. The functionalization at C7 and at C5 (with indoles bearing a chloro substituent at C5) is carried out by alkynylations, Suzuki–Miyaura cross-couplings, and Buchwald-Hartwig C–N bond forming reactions. One-pot protocols for the synthesis of 2, 5, 7-trisubstituted indoles from 2-aryl-7-bromo-5-chloroindoles as well as from 2-bromo-4-chloro-6-iodoaniline are also described. Graphical abstract: